Soil carbon dioxide emission associated with soil porosity after sugarcane field reform - de Souza, Luma Castro [UNESP]; Fernandes, Carolina [UNESP]; Moitinho, Mara Regina [UNESP]; da Silva Bicalho, Elton [UNESP]; la Scala, Newton [UNESP] (Springer Nature, 2018)
This study aimed to characterize soil carbon dioxide (CO2) emission associated with soil pore distribution in an Oxisol and Ultisol under chiseling in the planting row and in total area for sugarcane (Saccharum officinarum) cultivation. The experimental design was a large paired-plot design. Treatments consisted of chiseling in the planting row (CPR) and chiseling in total area (CTA) in an Oxisol and Ultisol. Soil CO2 emission, soil temperature, and soil moisture were assessed over 12 days in the Oxisol and 11 days in the Ultisol at a depth of 0–0.10 m. Organic carbon associated with minerals (OCAM) and particulate organic carbon (POC) were also assessed. OCAM, pore class C2 (0.05 ≤ ɸ < 0.1 mm), soil moisture, and soil temperature explained 72 and 53% of the variability of soil CO2 emission in CPR and CTA, respectively. In the Ultisol, pore class C1 (ɸ ≥ 0.1 mm) and OCAM explained 82% of the variability of soil CO2 emission in CPR. In CTA, soil moisture, OCAM, and POC explained 67% of the variability of soil CO2 emission. In the Oxisol, CPR and CTA affected soil structure, causing changes in both soil porosity and soil CO2 emission. In the Oxisol, the lowest average value of soil CO2 emission (2.8 μmol m−2 s−1) was observed in CPR whereas its highest value (3.4 μmol m−2 s−1) was observed in CTA. In the Ultisol, soil tillage (CPR and CTA) did not affect soil CO2 emission. These results indicate that the intensity of soil tillage in more clayey textured soils favors soil CO2 emission possibly due to a higher carbon availability for microbial activity when compared to more sandy textured soils. A less intensive soil tillage can be considered as an efficient strategy to reduce soil CO2 emission and hence soil organic carbon losses. Thus, this management strategy proved to be efficient in terms of mitigating greenhouse gas emissions, reducing the contribution of agriculture to global climate change.
Keywords: Carbon; Chiseling; Pore distribution; Soil moisture; Soil temperature